A REVIEW ON THE SYNTHETIC METHODOLOGIES OF CHROMONES - Vanguru, Mahathy; Merugu, Ramchander; Garimella, Swetha; E, Laxminarayana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Chromones group of compounds and their derivatives form the essential component of pharmacophores in many biologically active molecules. They exhibit a wide range of biological activities such as antibiotic, antitumor, antiviral, antioxidant, antipsychotic, and antihypoxic activities. These applications have stimulated a continuous search for the synthesis of new compounds in this field and are being extensively investigated. The various methodologies so far reported for the synthesis of these compounds with the compounds biological applications are discussed in this communication